"It's just a phase": Identity denial experiences, self-concept clarity, and emotional well-being in bisexual individuals. Issue 4 (19th May 2021) - Garr-Schultz, Alexandra; Gardner, Wendi
ABSTRACT: Bisexual individuals suffer poorer well-being than their gay and lesbian peers. The current work highlights the identity denial experiences of people who identify as gay, lesbian, and bisexual through self-reports and quantitative measures. Study 1 (N = 130) asked participants about unsupportive experiences during sexual identity disclosure and found that experiences of identity denial were more frequently reported by bisexual individuals compared to gay and lesbian peers. Study 2 (N = 202) examined the distinct relationship of identity denial experiences, above and beyond other prejudiced responses and discrimination, with well-being and self-concept outcomes. Results suggest identity denial is a frequent experience for bisexual individuals and is uniquely associated with lower psychological well-being and a less clear self-concept.